Cluster-based water level patterns detection - Friska Natalia Ferdinand; Yustinus Soelistio; Ferry Vincenttius Ferdinand; I Made Murwantara (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Indonesian Disaster Data and Information in 2016 showed that flood has reached a soaring 32.2% overall. In one of the common flood region (2016), Tangerang, the flood had impacted 30,949, and destroys more than 400 residentials. In spite of this dreadful fact, Tangerang has no systematically ways of detecting the flood patterns. Therefore, there is urgency for a system that is able to detect potential flood risks in Tangerang. This study explores a mean to systematically find flood patterns in Tangerang and attempt to visualize the risks based on 11 years of data on four major river stations within Tangerang vicinity. All the data obtained from Ciliwung Cisadane River Basin Center (BBWS) between 2009 until 2017 with total data of 368,184 rows. This study proposes an interactive dashboard based on the water level data covering rivers of Angke, Pesanggrahan, and Cisadane. Three clustering methods are implemented, the K-Medoids, DBScan, and x-means, to segregate the water level data, taken from four stations obtained from Ciliwung Cisadane River Basin Center (BBWS), into meaningfull periodic flood patterns. The output of this research is an interactive dashboard created based on the newly found patterns. The dashboard is designed to be simple and easy to use for non-technical persons. We believe that the output of this research could be implemented into the decision-making process taken by the Ciliwung Cisadane River Basin Center (BBWS) in order to improve countermeasure attempts on the potentially flooded areas.